Propidium Monoazide Combined With RT-qPCR Detects Infectivity of Porcine Epidemic Diarrhea Virus - Liang, Gong; Long, Yunzhi; Li, Qianqian; Yang, Liu; Huang, Ying; Yu, Daobing; Song, Wenbo; Zhou, Mingguang; Xu, Gaoyuan; Huang, Chao; Tang, Xibiao (Frontiers in Veterinary Science, 2022)
Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) allows sensitive detection of viral particles and viruses in epidemic samples but it cannot discriminate noninfectious viruses from infectious ones. Propidium monoazide (PMA) coupled with quantitative polymerase chain reaction (qPCR) was assessed to detect infectious viruses. Currently, there is no established test method to detect the infection of the porcine epidemic diarrhea virus (PEDV). In this study, propidium monoazide coupled with qPCR detects infectivity of PEDV. We optimized the method from the selection of primers, the working concentration of PMA, and the inactivation method using heat or ultraviolet (UV). The viruses which were treated with PMA before qPCR were inactivated using heat or UV. However, the addition of PMA alone did not affect the detection of live viruses, which indicates that a viral capsid break may be essential for PMA to bind to the genome. A repetition of the method on naked PEDV RNA suggests that it can be used to detect potentially infectious PEDV. The results indicated that an optimal plan of PMA could be extremely useful for evaluating infectious and noninfectious viruses.